My little pony, friendship is magic. Rarity [videorecording (DVD)]. (Shout! Kids, 2018)
"Celebrate Friendship Day with every pony's favorite fashionista not to mention Spike's #1 crush Rarity! Not only ids she always up to date on the latest trends and styles, Rarity is one of the most generous ponies you'll ever meet. See for yourself as Rarity along with her best friends Twilight Sparkles, Pinkie Pie, Rainbow Dash, Applejack, Fluttershy, and of course, Spike prepare for the Grand Galloping Gala, search for the loveliest of gems, investigate mysteries, and more!"-Container.